Brickets in A Review of The Philosophy of Science - Fithry, Dwi Annisa; Legawati, Lisa; Aulia Sari Ermal, Dini; Maarasyid, Cici; Jusnita, Jusnita; Salsabila, Naia; Febrian, Amanda (SURYA TEKNIKA, 2023)
Review draft briquettes in context philosophy knowledge this knowledge explains How to approach knowledge and can help us understand the production process, use, and impact environment briquettes. in perspective philosophy knowledge, production briquettes involve the use method scientific, like chemistry and engineering machines, to change biomass to become material burn solid. It involved understanding deep about traits chemistry and physics material standards, as well as the conversion process of energy. Impact environment from the use of briquettes. Using briquettes can influence the ecosystem and impact on the environment. Approach philosophy knowledge helps We dig questions about ethics use briquettes and effort to reduce the negative impact. The Aspect of social economy- related to the production and use of briquettes, like impact on the community local, and how knowledge can help understand the implications of this. This study gives an understanding deep about how briquettes can see through the lens of philosophical knowledge. This thing gives contribution is important in integrating knowledge, ethics, and impact socio-economic in understanding We technology energy alternatives like briquettes.